Risk factors in Angiographically Proven Coronary Patients - Rawat, B; Pandey, M; Acharya, Ramana; Satual, Archana; Sodhi, HS; Jha, Sunil C; Karki, D.B.; Kasliwal, R.R.; Pandey, Rajib (Nepalese Heart Journal, 2004)
CAD is coming as an epidemic in south east Asian countries. Yet recently coronary interventions have been almost non-existent in the Himalayan Kingdom of Nepal.To assess the local profile of the coronary disease, identify and establish the locally prevalent risk factors, coronary angiographic evaluation is mandatory. We recently completed 700 coronary angiograms in our institute.